Julio Llamazares o la historia que se borró = Julio Llamazares or the history that was deleted - Paleologos, Konstantinos (Estudios Humanísticos. Filología, 2017)
Julio Llamazares "habló" en su obra del ocaso de toda una civilización, la de los pueblos montañosos del norte de España que se vieron abandonados por sus pobladores a causa de la emigración masiva de los años 50 y 60, y nos enseñó que la Literatura puede ser, más que la Historia, la única manera posible de dar voz a seres que son los últimos de su estirpe. Julio Llamazares, in his work, "speaks" of the sunset of a whole civilization, that of the mountain villages of northern Spain which were abandoned by their inhabitants because of the mass immigration in the 1950s and 1960s, and showed us that Literature can be, even more than History, the only possible way to give voice to people who are the last of their generation.